Sensitive Gains of Rehabilitation Nursing Care in Elderly with Change of Mobility - Maria, Soares (2018)
Objectives: Acquire and develop skills in providing specialized care in Rehabilitation Nursing and evaluate the sensitive gains for Rehabilitation Nursing care in people with deficits in self-care due to mobility changes due to respiratory disease. Methodology: Qualitative approach and exploratory-descriptive nature. Interview, participatory observation based on the qualitative methodology of Robert Yin's case study and care methodology based on the medium-range theory of Professor Manuel José Lopes (2006). Participants were 3 people who were hospitalized in Internal Medicine - Silva Duarte Unit of the Hospital of São Bernardo, Setúbal. Data collection took place from 14 May 2018 to 22 June 2018. For the data treatment, the content analysis of Bardin (2009) was used. Results: improvement of "degree of functionality", "self-care" and "breathing function" in all patients undergoing rehabilitation nurse intervention. Conclusion: The interventions of the rehabilitation nurse allow to minimize the cause of immobility by improving the changes caused by the disease. The ENCS and the Barthel index are useful tools for assessing health gains in specialized rehabilitation care provided to the patient with respiratory pathology and associated comorbidities.